Foreign body in a Zenker’s diverticulum (looking for the lost dentures) - Naprawa, Grzegorz; Białkowska, Joanna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Zenker’s diverticulum (ZD), an acquired false pharyngoesophageal diverticulum, is a rare pathology. The prevalence of ZD among the general population is believed to be between 0.01% and 0.11%. Most patients are elderly men with symptoms of dysphagia. The most common treatments are open surgical diverticulectomy with or without cricopharyngeal myotomy and endoscopic myotomy. The authors report the case of a dental prosthesis lodged within an asymptomatic ZD in a 73-year-old man. It was safely removed endoscopically. So far, there have only been single reports of entrapment of an enteroscopy capsule lodged in a ZD in medical literature.